Strategic Solution Model Revitalization of the Role of Actor Network in Accelerating Stunting Rate Reduce in “Quality Family (KB)” Villages, Salatiga City - Daru Purnomo; Sri Suwartiningsih; Jodelin Muninggar; Suryo Sakti Hadiwijoyo (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
The city of Salatiga has launched "Rembug Stunting" as a program and at the same time as a stunting prevention movement that is being carried out at all levels of sub-districts in Salatiga City. Including status village as KB Village, including: KB Village, Kelurahan Kauman South, Kelurahan Blotongan, Kelurahan Kecandran, Kelurahan Kumpulrejo, and Kampung KB Kelurahan Thump Lor. Purpose of Research the action is to identify root problem causes of stunting in the five KB Villages, and conduct reinforcement and assistance DASHAT cadres (Kitchen Healthy Overcome Stunting) in the KB Village, Salatiga City. Research results action this show that root problem root causes of stunting from factor pattern care and development family, factor marriage age child, factor economics, diet and intake nutrition in Baduta (Baby lower two years) and Toddlers (infants under five years), Sanitation and other factors such as disease degenerative. Strengthening and mentoring DASHAT cadres through presentation anti stunting snack is strategy for overcome stunting on the level root grass so that motivating DASHAT cadres to practiced in life everyday, besides enhancement capacity from cadre that alone. Strategy role network actors also do through Learning program activities Field Integrated (PLT) through the "PENTING" Student program (Care for Stunting), promotion and branding of Kampung KB through social media accounts and making Kampung KB profile videos, developing them role active various elements in the Kampung KB community through outreach, education and advocacy about prevention of stunting, marriage age children and violence to child, as well develop network collaboration through Free Learning Independent Campus (MBKM).